Jerky Movement with Ceftazidime: A Case of Ceftazidime-Induced Neurotoxicity with a Review of the Literature. (12th December 2019) - Al-Sadawi, Mohammed; Rodriguez Ortega, Romy; Sun, Natalie; Abdurahimova, Madina; McFarlane, Samy I.
Abstract : Neurotoxicity manifested as confusion and seizures has been recognized as a side effect of multiple cephalosporins including ceftazidime. Renal impairment and inappropriate dosing are the most common contributors to the development of neurological abnormalities in patients receiving these antibiotics. The presence of baseline neurological abnormalities likely contributes to the frequency of these adverse events. Here, we present a case of a 78-year-old man that developed altered mental status and myoclonic movement after initiation of ceftazidime in the setting of mild renal dysfunction. Resolution of clinical picture was evident after 48 hours of discontinuation of the antibiotic without additional interventions.